2011
DOI: 10.1103/physrevb.83.161409
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional plasmon-phonon coupling in graphene

Abstract: We predict the existence of coupled plasmon-phonon excitations in graphene by using the selfconsistent linear response formalism. The unique electron-phonon interaction in graphene leads to unconventional mixing of plasmon and optical phonon polarizations. We find that longitudinal plasmons couple exclusively to transverse optical phonons, whereas graphene's transverse plasmons couple only to longitudinal optical phonons. This coupling can serve as a magnifier for exploring the electron-phonon interaction in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…Recent work has shown that flexural phonon modes have an essential role in thermal conductance in suspended graphene 36 . Graphene also has unusual and strong coupling between plasmons and phonons 37,38 . Thus, an inelastic collision may trigger a flexural phonon mode either directly or through plasmon coupling that causes a temporary increase in the out-of-plane motion of surrounding atoms, and if a subsequent elastic collision were to occur with one of these atoms then sputtering may result.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that flexural phonon modes have an essential role in thermal conductance in suspended graphene 36 . Graphene also has unusual and strong coupling between plasmons and phonons 37,38 . Thus, an inelastic collision may trigger a flexural phonon mode either directly or through plasmon coupling that causes a temporary increase in the out-of-plane motion of surrounding atoms, and if a subsequent elastic collision were to occur with one of these atoms then sputtering may result.…”
Section: Discussionmentioning
confidence: 99%
“…However, the excitation of intrinsic graphene plasmons allows the tuning of strong absorption into the mid-infrared [22][23][24] . Intrinsic graphene plasmons also produce high confinement of electromagnetic energy in sub-wavelength dimensions in combination with a longer lifetime of the excitation as compared with plasmons in metals 25 . Moreover, unlike surface plasmons in metals [18][19][20]26 , plasmons in graphene can be effectively tuned with a backgate voltage, potentially enabling optoelectronic switching devices.…”
mentioning
confidence: 99%
“…Plasmons are excited when the standing plasmon resonance of the graphene array, tuned by gate modulation of the chemical potential, coincides with a selected incident light frequency. These plasmons decay into hot electron-hole pairs via scattering from the edges of the nanostructures or via inelastic scattering with optical phonons 25,31 . Longer-lived hybrid plasmon-phonon modes that also have narrower spectral widths owing to the uncertainty principle can be induced through coupling with the underlying SiO 2 substrate 31,32 .…”
mentioning
confidence: 99%
“…It has many desirable properties such as gate-tunability, extreme light confinement, long plasmon lifetime, and plasmonic resonances in the terahertz to mid-infrared (IR) regime [8][9][10][11][12][13]. Spatially resolved propagating plasmons has been observed with scanning near-field optical microscope [14,15] In this paper, we discuss why Bernal AB-stacked bilayer graphene is important and interesting in its own right as a plasmonic material.…”
mentioning
confidence: 99%